When metabolism meets topology: Reconciling metabolite and reaction networks. - Montañez, Raúl; Medina-Torres, Miguel Ángel; Solé, Ricard V.; Rodríguez-Caso, Carlos Francisco (Wiley, 2010)
The search for a systems-level picture of metabolism as a web of molecular interactions provides a paradigmatic example of how the methods used to characterize a system can bias the interpretation of its functional meaning. Metabolic maps have been analyzed using novel techniques from network theory, revealing some non-trivial, functionally relevant properties. These include a small-world structure and hierarchical modularity. However, as discussed here, some of these properties might actually result from an inappropriate way of defining network interactions. Starting from the so-called bipartite organization of metabolism, where the two meaningful subsets (reactions and metabolites) are considered, most current works use only one of the subsets by means of so-called graph projections. Unfortunately, projected graphs often ignore relevant biological and chemical constraints, thus leading to statistical artifacts. Some of these drawbacks and alternative approaches need to be properly addressed.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/14547
Keywords: Bioinformática; Metabolismo - Simulación por ordenador; Computational Biology; Computer Simulation; Metabolism; Metabolic Networks; Complex networks